Exploring the Correlation Between Speaking Anxiety and English Oral Performance Among Nursing Students Using a Genre-Based Approach - Hendra Putra; Hartono, Rudi; Mujiyanto, Januarius; Yuliati (Universitas Hamzanwadi, 2025)
Speaking anxiety can impair nursing students’ ability to communicate effectively in English, especially in academic and clinical settings. This study examines the relationship between speaking anxiety levels and speaking performance among nursing students within a genre-based framework. The research was conducted at a private university in West Sumatra, Indonesia, involving all 33 third-year nursing students through total sampling. Using a quantitative one-group pretest–posttest design, data were collected with the Foreign Language Classroom Anxiety Scale (FLCAS) and speaking performance tests, then analyzed using Pearson’s product-moment correlation via SPSS 21. The results showed a weak positive but non-significant correlation between speaking performance and overall anxiety levels (r = 0.196, p = 0.309). Further analysis by anxiety categories revealed: (1) a very weak, non-significant correlation among students with high anxiety (r = 0.094, p = 0.772; n = 12); (2) a very weak, negative, non-significant correlation among students with moderate anxiety (r = –0.141, p = 0.698; n = 10); and (3) a moderate, but non-significant, positive correlation among students with low anxiety (r = 0.549, p = 0.202; n = 7). These findings suggest that, although some patterns are identifiable, speaking anxiety does not consistently or significantly impact students’ speaking performance. The study emphasizes the importance of considering individual differences in anxiety when developing genre-based speaking instruction for nursing education.